Simple approach based on ultrasound-assisted emulsification-microextraction for determination of polibrominated flame retardants in water samples by gas chromatography-mass spectrometry - Fontana, Ariel Ramón (2009)
A simple, efficient, innovative and environmentally friendly analytical technique was successfully applied for the first time for the extraction and preconcentration of polybrominated diphenyl ethers (PBDEs) from water samples. The PBDEs selected for this work were those most commonly found in the literature in natural water samples: 2,2′,4,4′-tetraBDE (BDE-47), 2,2′,4,4,5-pentaBDE (BDE-99), 2,2′,4,4,6-pentaBDE (BDE-100) and 2,2,4,4′,5,5′-hexaBDE (BDE-153). The extracted PBDEs were separated and determined by gas chromatography-mass spectrometry (GC-MS). The extraction/preconcentration technique is based on ultrasound-assisted emulsification-microextraction (USAEME) of a water-immiscible solvent in an aqueous medium. Several variables including, solvent type, extraction time, extraction temperature and matrix modifiers were studied and optimized over the relative response the target analytes. Chloroform was used as extraction solvent in the USAEME technique. Under optimum conditions, the target analytes were quantitatively extracted achieving enrichment factors (EF) higher than 319. The detection limits (LODs) of the analytes for the preconcentration of 10 mL sample volume were within the range 1-2 pg mL-1. The relative standard deviations (RSD) for five replicates at 10 pg mL-1 concentration level were <10.3%. The calibration graphs were linear within the concentration range of 5-5000 pg mL-1 for BDE-47 and BDE-100; and 5-10,000 pg mL-1 for BDE-99 and BDE-153, respectively. The coefficients of estimation were ≥0.9985. Validation of the methodology was performed by standard addition method at two concentration levels (10 and 50 pg mL-1). Recovery values were ≥96%, which showed a successful robustness of the analytical methodology for determination of picogram per milliliter of PBDEs in water samples. Significant quantities of PBDEs were not found in the analyzed samples.